Phenanthroline-bis-oxazole ligands for binding and stabilization of G-quadruplexes - Medeiros-Silva, João; Guédin, Aurore; Salgado, Gilmar F.; Mergny, Jean-Louis; Queiroz, João A.; Cabrita, Eurico J.; Cruz, Carla (Biochimica et biophysica acta. General subjects, 2017)
G-quadruplexes (G4) are found at important genome regions such as telomere ends and oncogene promoters. One prominent strategy to explore the therapeutic potential of G4 is stabilized it with specific ligands. We report the synthesis of new phenanthroline, phenyl and quinoline acyclic bisoxazole compounds in order to explore and evaluate the targeting to c-myc and human telomeric repeat 22AG G4 using FRET-melting, CD-melting, NMR, fluorescence titrations and FID assays. The design strategy has led to potent compounds (Phen-1 and Phen-2) that discriminate different G4 structures (human telomeric sequences and c-myc promoter) and selectively stabilize G4 over duplex DNA. CD studies show that Phen-2 binds and induces antiparallel topologies in 22AG quadruplex and also binds c-myc promotor, increasing their Tm in about 12°C and 30°C respectively. In contrast, Phen-1 induces parallel topologies in 22AG and c-myc, with a moderate stabilization of 4°C for both sequences. Consistent with a CD melting study, Phen-2 binds strongly (K=106 to 107M−1) to c-myc and 22AG quadruplexes. Phen-1 and Phen-2 discriminated among various quadruplex topologies and exhibited high selectivity for quadruplexes over duplexes. Phen-2 retains antiparallel topologies for quadruplex 22AG and does not induce conformational changes on the parallel c-myc quadruplex although Phen-1 favors the parallel topology. NMR studies also showed that the Phen-2 binds to the c-myc quadruplex via end stacking. Overall, the results suggest the importance of Phen-2 as a scaffold for the fine-tuning with substituents in order to enhance binding and stabilization to G4 structures. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. [Display omitted] •Phen-1 and Phen-2 G-quadruplex ligands have been synthesized and characterized.•Circular dichroism, FRET, fluorescence and NMR have been employed.•The compounds bind and stabilize specifically G-quadruplex structures.•Phen-2 is the most promising ligand for binding and stabilization G4.